Mengoptimalkan YouTube Kids di Perangkat Android sebagai Teman Aman Anak di SDS AR-RASYD - Syahputra, Irwan; Syahputra, Hindra; Putra, Heri Eko Rahmadi; Siregar, Erwin Syahputra; Iqbal, Muhammad; Khairul, Khairul (Jurnal Pengabdian Masyarakat Gemilang (JPMG), 2024)
This research explores optimal strategies for integrating YouTube Kids on Android devices as a safe learning companion for children. With the rapid growth of digital content, it is crucial to understand how to effectively leverage this platform to support a positive and secure experience for children. The research methodology involves the analysis of YouTube Kids usage, evaluation of safety features, and assessment of the impact on children's learning. Key findings include the identification of common usage patterns, the effectiveness of safety features in protecting children from inappropriate content, and recommendations for optimizing the learning experience. Practical implications of this research provide guidance to parents, educators, and policymakers to maximize the positive potential of YouTube Kids in supporting children's development in a safe and beneficial manner. By focusing on safety and education, this research contributes to the literature on the use of technology in the context of children's learning.